EXAMINING THE CULTURAL SIGNIFICANCE OF WAYANG KEBO GRINGSING PATTERN IN TENGANAN PEGRINGSINGAN TRADITIONAL VILLAGE FROM TRI HITA KARANA PERSPECTIVE - I Nengah Juliawan (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2023)
Woven fabric is one of the results of community culture and is one of the crafts that still survive in the midst of society, especially in Bali. One of the woven fabrics that has prestige value in Bali and even Indonesia is woven fabric with double ikat technique known as gringsing woven fabric. Gringsing woven fabric is the result of the original culture of the Bali Aga people, namely the Tenganan Pegringsing an Traditional Village. One of the gringsing woven fabrics is the gringsing wayang kebo motif which is considered exclusive because the motif contained in the fabric sheet is inspired by the story of the Mahabharata epic. This research is a qualitative type of research that produces descriptive data. In general, gringsing fabric has three basic colors, namely white, black and red, which explicitly symbolize the beliefs of Balinese Hindus called the trinity of the main gods, namely Tri Murti (Brahma, Vishnu and Shiva). The wayang kebo motif has a more complicated pattern than the gringsing barak motif in general, this is because there is a composition of shapes and colors that can be considered perfect in terms of style and in terms of the manufacturing process is quite complicated. The patterns contained in this wayang kebo gringsing cloth are believed to be the concept of life of the Tenganan Pegringsing an community which boils down to the philosophy of Tri Hita Karana, which is visualized in 3 large pattern forms namely (1) Main Pattern, (2) Middle Pattern, (3) Edge Pattern.Keywords: Culture, Woven fabric, Gringsing wayang kebo, Tenganan Pegringsing an, Tri Hita Karana.